The Influence of Good Corporate Governance (GCG) on Corporate Financial Performance: A Moderated Relationship by Firm Size - Naufal Nurrohmat; Bara Zaretta; Suhita Whini Setyahuni; Maria Safitri (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study is conducted to assess the relationship between Good Corporate Governance (GCG) practices and the financial performance of LQ45-listed companies, in which firm size plays a moderating role. A sample of 23 firms, consistently listed in the LQ45 index between 2019 and 2023, was utilized in this study. The selection of companies relied on purposive sampling as the selection technique. The analysis of the data was conducted by utilizing a regression model with a data panel, with the software EViews 13 being utilized for this purpose. The findings of the study demonstrated that independent commissioners contributed positively and significantly to the firm’s return on assets (ROA). Insider share ownership and board size demonstrated no significant impact. Conversely, ROA was adversely and significantly influenced by of the audit committee. The results of the moderation test demonstrate that the correlation between insider ownership and ROA is strengthened, while the correlation between independent board commissioners and ROA is weakened. Moreover, the study determined that the board size and the audit committee were not moderated by return on assets (ROA).